Assessment of fecal contamination and its potential risks of rainwater collected in Hanoi city, Vietnam - Nhu Da, Le; Thi Xuan Binh, Phung; Thi Mai Huong, Nguyen; Thi Thu Ha, Hoang; Thi Anh Huong, Nguyen; Thi Minh Hanh, Pham; Thi Thuy, Duong; Thi Phuong Quynh, Le (Vietnam Journal of Earth Sciences, 2025)
Fecal indicator bacteria (FIB) are used worldwide as indicators of fecal contamination in water, particularly in drinking water. This paper aims to investigate the level of FIB contamination and its associated public health risks in rainwater samples collected at 22 sites in inner-urban and suburban districts of Hanoi City during the period from May 2023 to May 2025. The results showed higher FIB values in inner-urban districts where high population densities were reported. The mean values of TC and EC in raw rainwater at most sites observed were higher than the limits of the Vietnam national technical regulation for domestic water use and also the WHO (2022) guideline for drinking water. A high public health risk was identified, and rainwater was unsuitable for direct potable use without treatment. Thus, our results underscore the importance of preventive and treatment measures to mitigate the risks associated with using harvested rainwater. Both natural and anthropogenic factors are primarily influencing the spread and persistence of FIB in this study. Our results provide a scientific basis for policy-making in air environmental protection for Hanoi City, as well as other large cities in developing countries in Asia.